Maksimalisasi Kinerja Pegawai Dengan Efek Penguatan Kepuasan Kerja - Adya Hermawati; Martaleni Martaleni; Totok Hendarto (EKONOMI & SOSIAL, 2021)
Triggered by the organizational restructuring of PT Indoperta Jawa Timur, this is a study of the influence of employee commitment, competence and work motivation on job satisfaction and employee performance. Uses an explanatory approach with quantitative and qualitative methods with descriptive analysis and Structural Equation Modeling (SEM) with the help of AMOS applications. The results obtained are there positive and significant influence between employee commitment variables on employee job satisfaction. That employee competence shows a positive direct effect on employee job satisfaction. That employee work motivation shows a positive but not significant direct effect on job satisfaction. That employee commitment shows a significant positive direct effect on employee performance. However, employee commitment is not a parameter in measuring employee performance through job satisfaction variables. That the competency variable shows a negative and insignificant direct effect on employee performance. This is the indirect effect through job satisfaction. Work motivation shows a positive and insignificant direct effect on employee performance. Likewise, the indirect influence through job satisfaction. Job satisfaction has a positive direct effect but not significant on employee performance.